Religious Moderation in Aceh: A Strategy for Implementing Islam Washatiyah Values in Acehnese Society - Syibran Mulasi; Syaibatul Hamdi; Muhammad Riza (Al-Adyan: Journal of Religious Studies, 2023)
This article aims to look at the reality of religious moderation in Acehnese society, the challenges in implementing moderation values and the solutions in introducing religious moderation in Acehnese society. This study uses a qualitative approach with data collection conducted by interviewing academics at PTKIN Aceh and observing the development of moderation in society, namely by examining religious symptoms and conflicts in Aceh. The results of the study show that the practice of religious moderation had developed in Aceh long before the term moderation was echoed by the center, Acehnese people very easily accept anyone to live side by side even if they have different beliefs. The Acehnese with the principle of "peumulia jame" can accept anyone with good intentions coming to Aceh. On the other hand the people of Aceh will rebel and fight if there are parties who disturb and want to change their local wisdom, such as bid'ah the Prophet's birthday, suing religious traditions that have been ingrained with the lure of heresy and heresy, of course this kind into resistance and resistance. To implement religious moderation in society, this can be done in a top-down manner, starting with religious leaders, the preachers and also the involvement of the Islamic campus in introducing the Islamic value of washatiyah in the community, besides that, gentle recitations using the mauidhatul hasanah method in the community so that by introducing this soft Islam will certainly hit the hearts of the Acehnese Muslim community. Artikel ini bertujuan untuk melihat realitas moderasi beragama pada masyarakat Aceh, tantangan dalam mengimplementasikan nilai-nilai moderasi dan solusi dalam memperkenalkan moderasi beragama pada masyarakat Aceh. Penelitian ini menggunakan pendekatan kualitatif dengan pengumpulan data dilakukan dengan mewawancarai akademisi di PTKIN Aceh dan mengamati perkembangan moderasi di masyarakat yaitu dengan mengkaji gejala dan konflik keagamaan di Aceh. Hasil kajian menunjukkan bahwa praktik moderasi beragama telah berkembang di Aceh jauh sebelum istilah moderasi didengungkan oleh pusat, masyarakat Aceh sangat mudah menerima siapapun untuk hidup berdampingan meskipun berbeda keyakinan. Masyarakat Aceh dengan prinsip “peumulia jame” dapat menerima siapa saja yang berniat baik datang ke Aceh. Di sisi lain masyarakat Aceh akan memberontak dan melawan jika ada pihak yang mengganggu dan ingin mengubah kearifan lokalnya, seperti bid'ah Maulid Nabi, menggugat tradisi keagamaan yang sudah mendarah daging dengan iming-iming kesesatan dan kesesatan, tentu saja hal semacam ini menjadi perlawanan dan perlawanan. Untuk mengimplementasikan moderasi beragama di masyarakat dapat dilakukan secara top-down, dimulai dari tokoh agama, ustadz dan juga keterlibatan kampus Islam dalam memperkenalkan nilai Islam washatiyah di masyarakat, selain itu pengajian yang lembut dengan menggunakan metode mauidhatul hasanah di masyarakat sehingga dengan mengenalkan Islam yang lembut ini tentu akan mengena di hati masyarakat muslim Aceh.